Effect of Aflatoxin B(1) on Cell Cultures - Gabliks, J. (1965)
Gabliks, J. (Massachusetts Institute of Technology, Cambridge), W. Schaeffer, L. Friedman, and G. Wogan. Effect of aflatoxin B(1) on cell cultures. J. Bacteriol. 90:720–723. 1965.—Aflatoxin B(1), a metabolite of the mold Aspergillus flavus, is toxic to cell cultures. The toxic effect is evidenced by an inhibition of growth followed by progressive granulation, rounding, and finally sloughing of the cells from the glass. In studies with embryonated eggs, duck embryos were found to be four to five times more susceptible than chick embryos. In studies on Chang liver cultures, there were decreases in cell number, protein, ribonucleic acid (RNA), and deoxyribonucleic acid (DNA) per culture with increasing aflatoxin B(1) concentrations. Since the cell number decreased and the protein, RNA, and DNA content per cell increased with increasing concentrations of aflatoxin, enlarged cells were suggested. These data are consistent with in vivo data of other workers who have found hypertrophic cells with enlarged nuclei in histological studies on the tissues of rats and ducklings fed toxic peanut meal.